PROPOSED MARKETING STRATEGY FOR PHOTOGRAPHY BUSINESS (The Indonesian Journal of Business Administration, 2019)
Since the beginning of the 2000s until now, the development of technology certainly can’t be separated from human daily life. The variety of cameras also increase from DSLR cameras to smartphone cameras can be used by anyone to capture the best moments with those who closest to them. Eunoia Verde Picture House is one of the photography service companies that participate in this market competition, especially for Bandung region and its surrounding areas. In carrying out business activities for companies that have only been running for 2 years, they always experiencing some problems, especially in aspects of stagnant income and uncertain sales. This study aims to determine the right strategy to deal with the problem. To overcome this problem, Eunoia Verde has several strategies that are suitable to be implemented. Among them are remodeling the marketing mix to be more concrete because it has been adjusted to surveys and benchmarks. Eunoia Verde is also looking for suitable strategies using Brand Touchpoint Wheel primarily to create consumer loyalty. From before the consumer makes a purchase until after the purchase, the process must be exercised so that the consumer experience while interacting with Eunoia Verde has the increase level of satisfaction.Keywords: photography, marketing strategy, marketing strategy, brand touchpoint.